Kajian produksi budidaya udang vaname di Kabupaten Kolaka - Yulianingsih, Tri; Budiyanto; Riani, Irdam; Hamzah, Muhaimin; Mansyur, Akhmad; Sarifin, Abdul (Jurnal Sosial Ekonomi Perikanan, 2022)
The purpose of this study was to determine the effect of land area, number of fry, amount of feed, amount of fertilizer, amount of lime, and amount of mill technology on production of vaname shrimp in Samaturu and Latambaga districts, Kolaka Regency from June to July 2020. The population in this study, all cultivators who are active in aquaculture activities totaling 17 people. The sample in this study was taken using the census method. Data collection in this study used interviews, observation, and documentation. Analysis of the data used is multiple linear regression analysis using SPSS 16.0. The results of the f-test analysis showed that all independent variables (land area, number of fry, amount of feed, amount of lime, amount of fertilizer, and amount of mill technology) used in this study simultaneously gave a significant effect on the dependent variable (production). Meanwhile, the test analysis shows that the production variable is significantly and not significantly affected. Variable area of ​​land and the number of fry have a significant effect on the production of vaname shrimp, while the amount of feed, the amount of lime, the amount of fertilizer, and the amount of mill technology have no significant effect on the production of white shrimp.